2020
DOI: 10.2478/nor-2020-0001
|View full text |Cite
|
Sign up to set email alerts
|

Mimicking News: How the credibility of an established tabloid is used when disseminating racism

Abstract: This article explores the mimicking of tabloid news as a form of covert racism, relying on the credibility of an established tabloid newspaper. The qualitative case study focuses on a digital platform for letters to the editor, operated without editorial curation pre-publication from 2010 to 2018 by one of Denmark’s largest newspapers, Ekstra Bladet. A discourse analysis of the 50 most shared letters to the editor on Facebook shows that nativist, far-right actors used the platform to disseminate fear-mongering… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…The normalisation is also facilitated by "novel" combinations of various argumentative frames which, in turn, allow for "new" and radical interpretations of ideas and concepts to be put forward. This implies that Swedish news media are not immune to the wider populist currents visible in other national media contexts in Scandinavia (Farkas & Neumayer, 2020), and that they also follow the normalisation of uncivil and populist discourses which "gradually introduce and/or perpetuate in public discourse some new patterns of representing social actors, processes and issues" (Krzyżanowski, 2020b: 432).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The normalisation is also facilitated by "novel" combinations of various argumentative frames which, in turn, allow for "new" and radical interpretations of ideas and concepts to be put forward. This implies that Swedish news media are not immune to the wider populist currents visible in other national media contexts in Scandinavia (Farkas & Neumayer, 2020), and that they also follow the normalisation of uncivil and populist discourses which "gradually introduce and/or perpetuate in public discourse some new patterns of representing social actors, processes and issues" (Krzyżanowski, 2020b: 432).…”
Section: Discussionmentioning
confidence: 99%
“…They draw on a peculiar set of affordances created by so-called borderline discourse (Krzyżanowski & Ledin, 2017), which gradually migrated from online and fringe spaces of uncivil society into mainstream politics and the media. This discourse -effectively placing uncivil opinions and ideas (such as anti-immigration expressed via racism and xenophobia) in frames of civil discourse (of democracy, nation-state, freedom of speech, rationalism, and the like) -has, to a large extent, allowed furthering nativism and right-wing nationalism in mainstream domains (see also Farkas & Neumayer, 2020).…”
Section: Racism Populist Strategy and The News Mediamentioning
confidence: 99%
See 1 more Smart Citation
“…Also, news published on what can be described as uncivil arenas may be conveyed through expressions that might, at first glance, seem civil. For instance, hateful discourses might be disguised by far-right actors by mimicking "real news" (Farkas & Neumayer, 2020). Studies have shown how far-right actors, rather than making up stories, often depend heavily on content from established news sources (Ekman, 2019;Haller & Holt, 2019;Krzyżanowski & Ledin, 2017).…”
Section: Uncivil News In Far-right Alternative Mediamentioning
confidence: 99%
“…Research has critically addressed the development of such illiberal trajectories in Denmark, with special attention paid to the ways the media contribute to these phenomena (Farkas & Neumayer, 2020;Lentin & Titley, 2011;Yilmaz, 2016). The class dimension of liberal racism, however, remains understudied.…”
Section: Theoretical Anchoringmentioning
confidence: 99%